A modified weighted function method for parameter estimation of Pearson type three distribution. Issue 4 (10th April 2014) - Liang, Zhongmin; Hu, Yiming; Li, Binquan; Yu, Zhongbo
Abstract In this paper, an unconventional method called Modified Weighted Function (MWF) is presented for the conventional moment estimation of a probability distribution function. The aim of MWF is to estimate the coefficient of variation (CV) and coefficient of skewness (CS) from the original higher moment computations to the first‐order moment calculations. The estimators for CV and CS of Pearson type three distribution function (PE3) were derived by weighting the moments of the distribution with two weight functions, which were constructed by combining two negative exponential‐type functions. The selection of these weight functions was based on two considerations: (1) to relate weight functions to sample size in order to reflect the relationship between the quantity of sample information and the role of weight function and (2) to allocate more weights to data close to medium‐tail positions in a sample series ranked in an ascending order. A Monte‐Carlo experiment was conducted to simulate a large number of samples upon which statistical properties of MWF were investigated. For the PE3 parent distribution, results of MWF were compared to those of the original Weighted Function (WF) and Linear Moments (L‐M). The results indicate that MWF was superior to WF and slightly better than L‐M, in terms of statistical unbiasness and effectiveness. In addition, the robustness of MWF, WF, and L‐M were compared by designing the Monte‐Carlo experiment that samples are obtained from Log‐Pearson type three distribution (LPE3), three parameter Log‐Normal distribution (LN3), and Generalized Extreme Value distribution (GEV), respectively, but all used as samples from the PE3 distribution. The results show that in terms of statistical unbiasness, no one method possesses the absolutely overwhelming advantage among MWF, WF, and L‐M, while in terms of statistical effectiveness, the MWF is superior to WF and L‐M.